Reciprocating wear of mild steel carburized using Na2co3-Nacl under lubrication - Willey Y.H. Liew; R. Protasius; Jester L.J. Ling; Nancy Julius Siambun; Chua, Bih Lii; Melvin Gan Jet Hong (Taylor & Francis Online, 2024)
The tribological behavior of non- and carburized mild steel under oil lubrication was investigated. 2 types of carburized steel specimens were used in this study. The surface of the first type of the carburized steel was rich in retained austenite. Towards the core, the amount of austenite reduced, and the amount of martensite increased. In contrast, the surface and subsurface of the second type carburized steel was rich in martensite. In the sliding tests carried out under hydrodynamic lubrication, the COF was found to reduce with increased load before boundary lubrication occurred at loads above 150 N. Under boundary lubrication at 1000 N, the martensite in the carburized layer reacted with the hydrocarbon and oil additive to form a lubricant film consisting of C-C, C=O, C-P, and C-O. This resulted in reduced COF and wear rate, if catastrophic fracture did not take place. The average COF and wear rate obtained at this load was 0.085–0.096 and 1.69–0.94 × 10−11 mm3 / Nm, respectively, lower than those that obtained at 600 N which were 0.108–0.109 and 2.89–4.86 × 10−11 mm3 /Nm, respectively. The lubricant film formed on the retained austenite, which involved only limited reaction with the hydrocarbon to form C-C, C=O, did not produce any such beneficial effect. These results showed that the presence of the retained austenite made the worn surface less favorable to form an effective anti-wear lubricant film.